Analisa Studi Keandalan Sistem Distribusi 20 kV di PT. PLN (Persero) UP3 Cempaka Putih Jakarta Pusat Menggunakan Metode FMEA (Failure Mode Effect Analysis) - Pratama, Rama Widi; Wati, Trisna (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
The increasing need for electric power demands a higher level of reliability in the power supply and distribution. This research aims to calculate the reliability level of the 20kV distribution system at PLN Ltd., UP3 Cempaka Putih, Central Jakarta, especially at the wind feeder in 2021, by implementing FMEA (Failure Mode Effect Analysis). Before using the FMEA method, SAIFI 1.15 times per year and SAIDI 3.9 hours per year. After using this method, the wind feeder reliability index value got SAIFI 1.09 times/year; SAIDI 3.5 hours/year; CAIFI 0.33 times/outage; CAIDI 3 hours/year; ASAI 99.95%. The undistributed energy due to wind feeder outages in 2021 reached 55694.46 kWh. With an economic loss value of IDR 88,507,867.71, the highest RPN (Risk Priority Number) value occurred at the damaged cut-out of 162.